DUA BATU BERHIAS DARI RUAS SUNGAI OPAK: DATA TAMBAHAN PEMBANGUNAN PERCANDIAN PRAMBANAN - Setianingsih, Rita Margaretha (Berkala Arkeologi, 1998)
Two ornate stones from the Opak River are interesting to observe. Until now it is seen that each has a different function and meaning. BG. 748 decorated stone which contains the attributes of the deity, namely vajra, trident and padma which can all be associated with Shiva. Similarly with the ancient Javanese script which mentions na - ma - kha. The noun relates to yogis to attain a level of inner purity by doing good deeds and contemplation of God. The yogis do this by using a means called a yantra. Similarly, with the writing of kha is a symbol of the sankhya which is related to the position of the moon and stars which are 27 pieces, in accordance with the number of BG. 748. The circle in the middle may symbolize candra, making it possible if BG. 748 is a candramandala which is one of the yantra as well as a description of the typical nature of the god Shiva.